INTERPRETATION OF FAMILY AND FAMILY RELATIONSHIP IN WRITINGS OF ORIENTAL THINKERS. - Imomqulova, Fotima (Журнал Педагогики и психологии в современном образовании, 2022)
Family and family relationships, especially, mutual relationship between wife and husband in a family is continuing to be one of actual problems (tasks) which has a prior demand for studying and investigating. At present time, changes in all sectors of society and stages of rebuilding it, couples which are getting married and establishing a worthy family relationhave vital position in our society, in which interrelation between wife and husband, their unity, understanding each other means nourishing those families and good psychological surroundin.